Flexoelectric Effect in the Reversal of Self‐Polarization and Associated Changes in the Electronic Functional Properties of BiFeO3 Thin Films. (30th July 2013) - Jeon, Byung Chul; Lee, Daesu; Lee, Myang Hwan; Yang, Sang Mo; Chae, Seung Chul; Song, Tae Kwon; Bu, Sang Don; Chung, Jin‐Seok; Yoon, Jong‐Gul; Noh, Tae Won
<x xml:space="preserve">Abstract</x> Flexoelectricity can play an important role in the reversal of the self‐polarization direction in epitaxial BiFeO3 thin films. The flexoelectric and interfacial effects compete with each other to determine the self‐polarization state. In Region I, the self‐polarization is downward because the interfacial effect is more dominant than the flexoelectric effect. In Region II, the self‐polarization is upward, because the flexoelectric effect becomes more dominant than the interfacial effect. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>